Vinnie Ream and Richard Leveridge Hoxie papers - Ream, Vinnie, 1847-1914.; Hoxie, R. L. (Richard Leveridge), 1844-1930.
Correspondence, memoranda, writings, reports, notebooks, commissions, biographical data, printed material, and other papers pertaining chiefly to Ream's work following her commission to execute the statue of Abraham Lincoln now standing in the U.S. Capitol rotunda. Other topics include racial conditions after the Civil War and social life in Washington, D.C., during Reconstruction. Papers (1853-1937) of Ream's husband Richard Leveridge Hoxie include material pertaining to Hoxie's Civil War service and two notebooks kept while serving on the Geographical Surveys West of the 100th Meridian led by George M. Wheeler. Includes a map said to have been carried by William T. Sherman on his march to the sea during the Civil War. Correspondents include George Caleb Bingham, Elias A. Boudinot, Georg Morris Cohen Brandes, Olivia Briggs, Ezra Cornell, Elizabeth Bacon Custer, Jubal Anderson Early, G.P.A. Healy, Joaquin Miller, Crosby Stuart Noyes, Albert Pike, David D. Porter, James S. Rollins, Edmund G. Ross, Alexander Robey Shepherd, William T. Sherman, Thaddeus Stevens, and Daniel W. Voorhees.
Microfilm edition of containers 1-3, 8) available
Microfilm from originals in the Manuscript Division
Microfilm of originals of the Vinnie Ream Hoxie file in the office of the U.S. Architect of the Capitol.
U.S. Architect of the Capitol
Library of Congress Prints and Photographs Division.
Library of Congress Rare Book and Special Collections Division.
Keywords: Bingham, George Caleb, -- 1811-1879 -- Correspondence; Boudinot, Elias A. -- Correspondence; Brandes, Georg, -- 1842-1927 -- Correspondence; Briggs, Olivia -- Correspondence; Cornell, Ezra, -- 1807-1874 -- Correspondence; Custer, Elizabeth Bacon, -- 1842-1933 -- Correspondence; Early, Jubal Anderson, -- 1816-1894 -- Correspondence; Healy, G. P. A. -- 1813-1894 -- Correspondence; Lincoln, Abraham, -- 1809-1865 -- Statues; Miller, Joaquin, -- 1837-1913 -- Correspondence; Noyes, Crosby Stuart, -- 1825-1908 -- Correspondence; Pike, Albert, -- 1809-1891 -- Correspondence; Porter, David D. -- 1813-1891 -- Correspondence; Rollins, James S. -- 1812-1888 -- Correspondence; Ross, Edmund G. -- 1826-1907 -- Correspondence; Shepherd, Alexander Robey, -- 1835-1902 -- Correspondence; Sherman, William T. -- 1820-1891.; Sherman, William T. -- 1820-1891 -- Correspondence; Stevens, Thaddeus, -- 1792-1868 -- Correspondence; Voorhees, Daniel W. -- 1827-1897 -- Correspondence; Wheeler, George M. -- 1842-1905.; United States. -- Army. -- Corps of Engineers; Geographical Surveys West of the 100th Meridian (U.S.); United States Capitol (Washington, D.C.); Military engineering; Race relations; Reconstruction (U.S. history, 1865-1877) -- Washington (D.C.); Sculpture; Sherman's March to the Sea; Statues -- Washington (D.C.); Surveys; Georgia -- History -- Civil War, 1861-1865.; Washington (D.C.) -- Social life and customs; United States -- History -- Civil War, 1861-1865 -- Campaigns; Army officers; Sculptors